2016
DOI: 10.1177/1359105314562084
|View full text |Cite
|
Sign up to set email alerts
|

Managing psychological stress in the multiple sclerosis medical visit: Patient perspectives and unmet needs

Abstract: Psychological stress can negatively impact multiple sclerosis (MS). To further understand how stress is addressed in the MS medical visit, 34 people with MS participated in focus groups. Transcripts were analyzed by inductive thematic analysis. The majority of participants did not discuss stress with their provider, citing barriers to communication such as lack of time, poor coordination between specialties, physician reliance on pharmaceutical prescription, and patient lack of self-advocacy. Participants reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Provision of emotional support is crucial to this process and is facilitated through listening to patients and acknowledging their experiences of living with diabetes . Indeed, patients have clearly indicated that they want their experiences of stress acknowledged and validated by professionals . Empathy therefore has an important role to play in communicating successfully with patients.…”
Section: Management Of Distress: Individual Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Provision of emotional support is crucial to this process and is facilitated through listening to patients and acknowledging their experiences of living with diabetes . Indeed, patients have clearly indicated that they want their experiences of stress acknowledged and validated by professionals . Empathy therefore has an important role to play in communicating successfully with patients.…”
Section: Management Of Distress: Individual Interactionsmentioning
confidence: 99%
“…Diabetes is an ongoing event and life circumstances will change, including perceived ability to cope, which will impact on patients perceived levels of diabetes distress at any one time. In addition, patients report wanting follow‐up and behavioural support for goals achieved, they value some accountability to professionals who are interested in their progress and can help them with problem‐solving regarding their concerns . In fact, retrospective data suggest that supporting people with reassurance at diagnosis, along with clear action plans, resulted in better self‐care 1–5 years after diagnosis, as well as less diabetes distress .…”
Section: Management Of Distress: Individual Interactionsmentioning
confidence: 99%
“…Similar findings have been reported in patients with multiple sclerosis (MS) in terms of their choice of disease-modifying therapy [27]. Negative communication experiences have led to some patients with MS perceiving their neurologists as having little interest in their day-to-day ongoing difficulties and stress [28,29].…”
Section: Discussionmentioning
confidence: 60%
“…Since the 1960s, the medical community has been looking for ways to prevent (primary prevention) and treat (secondary prevention) cardiovascular disease through management of cholesterol levels. 1 , 2 In reducing the risk for coronary heart disease, lowering low-density lipoprotein cholesterol (LDL-C), raising high-density lipoprotein cholesterol (HDL-C), and lowering triglycerides appeared to have the potential for reducing both morbidity and mortality. 3 Multiple categories of medications have been developed to manage lipid profiles and reduce the risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%